Christ Grown into Perfection. Hebrews 9,11 from a Christological Point of View - Fuhrmann, Sebastian (Biblica, 2008)
The author suggests a Christological reading of Heb 9,11 in the sense that the genitive tw~n genome&nwn a)gaqw~n is understood as a genitivus qualitatis referring to the virtues that Christ obtained during his earthly life through his suffering. With regard to the problem of textual criticism, the interpretation argues for genome&nwn instead of mello/ntwn.